Self-assembled metal cluster-carbon quantum dot heterostructures with photothermal antibacterial properties - Xulei Yuan; Shaojun Liu; Jun Wang; Jiaqi Liu; Fang Qin; Min Zhang; Jinling Song; Xiang Mao (Discover Nano)
Abstract Noble metal (Au, Ag, Cu) cluster is an emerging category of promising interest functions in form of designed constructions. Among various candidates, carbon dots could be treated as one interesting component for synthesis functional candidates while heterogeneous contents are orderly integrated together. In this work, we successfully fabricate heterostructural nanoparticles (HNPs) based on noble metal clusters (Au, Ag and Cu) integrated with carbon quantum dots (CQDs) through self-assembling approach. These HNPs demonstrate remarkable photothermal efficiency, high stability, low hemolysis ratio, excellent biocompatibility and significant bactericidal effects, making them promising candidates for photothermal applications. Notably, the Au–C achieved remarkable photothermal conversion efficiency (PTE) of 54.16% and antibacterial rate over 99%, which also significantly accelerated the healing process in methicillin-resistant Staphylococcus aureus (MRSA)-infected subcutaneous abscess model mice. Our findings highlight the potential of these self-assembled heterostructures, especially Au–C, as effective and promising photothermal agents with antibacterial functionality. Graphical Abstract